Forest management models based on linear programming. An application to Navafría forest (Segovia, Spain) - Diaz Balteiro, L.; Prieto Rodriguez, A. (Forest Systems, 1999)
This paper illustrates how analytical methods like linear programming can be fruitfully applied to forest management problems. This kind of approach is rather ignored in Spain. In fact, since last century Spanish forests have been managed with the help of German methods, which are not supported by any optimisation model. A linear programming model is built and applied to the Spanish forest Navafría. This forest has been chosen for our exercise because it has been deeply studied with the help of classic methods, so that different methodologies can be compared. Four objectives functions have been defined. Two are typically linked to silvicultural goals: maximise the total timber volume and veneer volume, and the other two show economic targets: maximise the net present value and maximise a similar cash flow in each period. Several constraints have been introduced. In all cases except one a feasible solution was found. Besides, a sensitivity analysis have been incorporated in order to check the influence of variations of the discount rate and expected wood price. The management alternatives proposed in this paper show harvest flows longer than the harvest flow indicated in the management project. In short, the results generated in our application by classic (German) methods can be considered a particular case of the results provided by the optimisation models based upon linear programming.